A COMUNICAÇÃO PUBLICITÁRIA NAS INSTITUIÇÕES FINANCEIRAS PARA O SEGMENTO DE ALTA RENDA - Montresor, Paulo Eduardo Noronha (2007)
This research is about how four of the biggest bank in Brazil - Bradesco, Itaú, Citibank e BankBoston they use the communication to seduce the public of high income. The objective is to define which are the appeals and the values used in the commercial ones of television and to understand why the films are many similarities in the persuasion arguments. The importance of this research it defines in consequence of the strong presence of the banks in the TV ways and for the fact of the main banks in Brazil to have launched in a short space of time sub marks, a resource very used by the industry with the extensions of marks, to take care of to a market of high income esteem in 2 million people. This is a new subject and still little explored in the academy. The used methods had been the content analysis, that verified the arguments of TV commercials and the bibliographical research, that the necessary ballast for the definition of the problem gave and based the resulted structuralized of the study the main ones of the research had presented the conversion of two trends; the first one comes of the new values that blow of the society, especially of the people of high income in Brazil. They have presented new forms of consumption, that are much more on to the emotions. The ostentation and the consumption of sophisticated products as synonymous of status and power continue and possibly they will have to continue to exist, but it notices now that the least has broken of the Brazilian elite search if to differentiate for subjective values. They are in return the basic values of the society as familiar relationship, valuation of the simple things and better exploitation of the time. On the other hand, the second trend is marketing. With the commoditization of the products and services, the companies search if to differentiate for the mark and, to make the connection of this with the consumers, emotional arguments are used. Even because, to be manipulated the consumers, the way most efficient is through the emotion. It can also be said that, to pierce the mental blockade that the consumers raise in virtue of the bombing of messages that receive daily, the way are to entertain, to move. Ally to everything this, the banks prays of negative image in the society and comes working to minimize this perception: they want for intermediary of its messages advertising executives if to become more likeable, human. When congregated these movements - of the society valuing more the being of what having and the banks wanting to humanize itself and using emotional appeals in its communication - it is easy to understand the similarity of arguments. But it will be that the differentiation lack will not continue bringing the commoditization of the products and services for the commoditization of the communication and making with that it leaves to fulfill one of its basic papers that are to make an advertiser if to differentiate of the competition?